Assessment of spatial and temporal changes in groundwater quality in a rural municipality using the CCME WQI water quality indicator - Balla, Dániel; Kiss, Emőke; Zichar, Marianna; Mester, Tamás (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
Urban groundwater pollution is a global phenomenon requiring several environmental measures to reduce. In our study, we investigated the changes in water quality following the construction of a sewerage network in a municipal setting between 2013 and 2022 in a long-term monitoring framework by regularly sampling 40 municipal groundwater wells. The changes in groundwater levels before (2013) and after (2017, 2022) the construction of a sewerage network were assessed based on the groundwater levels measured during the sampling. In 2013, the groundwater level was very close to the surface (
Keywords: water quality index; Báránd; monitoring data; GIS